2018
DOI: 10.3390/polym10090990
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Thermal Properties of Calcium Alginate/Reduced Graphene Oxide Composites

Abstract: Calcium alginate (CaAlg) is a kind of biodegradable and eco-friendly functional material, and CaAlg/reduced graphene oxide (rGO) composites are expected to be applied as new textile, heat-generating, and flame-retardant materials. In this paper, the CaAlg/rGO composites were prepared by a sol-gel method and their morphological and thermal properties were studied. The results showed that the introduction of rGO can efficiently improve the thermal stability of CaAlg. Further study showed that rGO increased the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…The first peak around 185 °C is associated with dehydration reactions in the alginate; while the second one, at 278 °C, corresponds to the degradation of the CaCO3. Likewise, the weight loss below 300 °C is caused by the loss of hydroxyl groups (-OH) in the alginate, and above this temperature decarboxylation reactions take place forming CO2 as the main product [29]. When BO is confined into the CaAlg capsules (BO Cap_2% and BO Cap_3%) the TGA Likewise, the weight loss below 300 • C is caused by the loss of hydroxyl groups (-OH) in the alginate, and above this temperature decarboxylation reactions take place forming CO 2 as the main product [29].…”
Section: Chemical and Thermal Properties Of The Bo Capsules And Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…The first peak around 185 °C is associated with dehydration reactions in the alginate; while the second one, at 278 °C, corresponds to the degradation of the CaCO3. Likewise, the weight loss below 300 °C is caused by the loss of hydroxyl groups (-OH) in the alginate, and above this temperature decarboxylation reactions take place forming CO2 as the main product [29]. When BO is confined into the CaAlg capsules (BO Cap_2% and BO Cap_3%) the TGA Likewise, the weight loss below 300 • C is caused by the loss of hydroxyl groups (-OH) in the alginate, and above this temperature decarboxylation reactions take place forming CO 2 as the main product [29].…”
Section: Chemical and Thermal Properties Of The Bo Capsules And Theirmentioning
confidence: 99%
“…Likewise, the weight loss below 300 °C is caused by the loss of hydroxyl groups (-OH) in the alginate, and above this temperature decarboxylation reactions take place forming CO2 as the main product [29]. When BO is confined into the CaAlg capsules (BO Cap_2% and BO Cap_3%) the TGA Likewise, the weight loss below 300 • C is caused by the loss of hydroxyl groups (-OH) in the alginate, and above this temperature decarboxylation reactions take place forming CO 2 as the main product [29]. When BO is confined into the CaAlg capsules (BO Cap_2% and BO Cap_3%) the TGA profiles of the BioPoly and that of the capsules containing the BO are very similar until 175 • C. Above 175 • C, the decomposition of the BO starts showing a DTG shoulder at Tsh = 190 • C, which could be attributed to the breakage of C-H and C-O-H in lighter molecules, such as carboxylic acids, and, to some extent, to the decomposition of the alginate itself.…”
Section: Chemical and Thermal Properties Of The Bo Capsules And Theirmentioning
confidence: 99%
“…This oxidative degradation/burning step is also confirmed by series of overlapped exothermic peaks. 44,45 The small mass loss step above 668.39 C (Δm −1.2%) corresponds to the degradation of the calcium carbonate, which was formed previously during the oxidative degradations of the calcium alginate. From thermal point of view, coconut oil is a little bit more stable, compared to the calcium alginate.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Zhao et al reported preparation of graphene modified calcium alginate composite using sol–gel process. The composite showed improved thermal stability and increased carbon formation, thus showed notable promise as multifunctional smart textiles having good fire retardancy and heat generating ability …”
Section: Graphene Modified Textile Composites In Relevant To the Propmentioning
confidence: 99%